2010
DOI: 10.1007/s10751-010-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

Penning trap mass measurements of transfermium elements with SHIPTRAP

Abstract: Penning traps are widely used for high-precision mass measurements of radionuclides related to nuclear astrophysics studies and the evolution of nuclear structure far away from stability. With the stopping of secondary beams in gas cells together with advanced ion-beam manipulation techniques their reach has been extended to rare isotopes of essentially all elements. The Penning trap mass spectrometer SHIPTRAP at GSI Darmstadt has recently demonstrated that even highprecision mass measurements of transfermium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Other highlights are: the first application of the Ramsey technique to on-line mass spectrometry [151][152][153]; the further development of the technique of isochronous mass spectrometry and its application to neutron-rich radionuclides at the Experimental Storage Ring ESR at GSI, which now reaches an uncertainty of typically 10 −6 [154]; the very large number of masses of isotopes of refractory elements determined at Jyväskylä by Penning trap mass spectrometry (for which only some references can be given here); the first mass measurement of 147 Tm, a nuclide beyond the proton-drip line [155] and the first mass determination of isotopes heavier than uranium, as reported by Michael Block for 252−254 No [111,156], which were created by fusion reactions and measured at SHIPTRAP; and, finally, high-accuracy tests of the isobaric multiplet mass equation with ISOLTRAP [157], LEBIT [104,158], and JYFLTRAP [159].…”
Section: Recent Developments and Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other highlights are: the first application of the Ramsey technique to on-line mass spectrometry [151][152][153]; the further development of the technique of isochronous mass spectrometry and its application to neutron-rich radionuclides at the Experimental Storage Ring ESR at GSI, which now reaches an uncertainty of typically 10 −6 [154]; the very large number of masses of isotopes of refractory elements determined at Jyväskylä by Penning trap mass spectrometry (for which only some references can be given here); the first mass measurement of 147 Tm, a nuclide beyond the proton-drip line [155] and the first mass determination of isotopes heavier than uranium, as reported by Michael Block for 252−254 No [111,156], which were created by fusion reactions and measured at SHIPTRAP; and, finally, high-accuracy tests of the isobaric multiplet mass equation with ISOLTRAP [157], LEBIT [104,158], and JYFLTRAP [159].…”
Section: Recent Developments and Highlightsmentioning
confidence: 99%
“…The first direct mass measurements of the nobelium isotopes 252−254 No have demonstrated that a production yield as low as 1 ion/s is sufficient [111,156]. Usually, a very strong contamination by isobaric ions or molecules prevents one from reaching such a low limit.…”
Section: Trends and Future Directionsmentioning
confidence: 99%
“…A strong homogeneous axial magnetic field provides confinement in the radial direction while axial confinement of the ions is achieved by a quadrupolar electric field. Penning traps are often used for precision studies such as the measurements of magnetic moments of the free electron [4,5], the electron in hydrogen-like ions [6][7][8], the electron in lithium-like ions [9,10], the positron [11], the proton [12][13][14] and the anti-proton [15][16][17][18], as well as measurements of the atomic mass of the electron [19][20][21], measurements of the proton-to-electron mass ratio [22][23][24] and high-precision mass measurement of stable as well as short-lived radionuclides [25][26][27][28]. These applications require the confining fields to be highly precise.…”
Section: Introductionmentioning
confidence: 99%